Peranan Guru Geografi Dalam Pembentukan Nilai-Nilai Karakter Melalui Pembelajaran Daring Kelas XI IPS 2 Di MAN 1 Palu - Abdul Hamid; Dj. Aluy, Sitti Magfirah (Jurpis: Jurnal Pendidikan Ilmu Sosial, 2021)
The formulation of the problem in this research is how the role of the teacher of geography and what are the inhibiting factors faced by teachers of geography in the formation of character values through online learning class XI IPS 2 MAN 1 Palu. Type descriptive qualitative research with the percentage. The subject in this research is the teacher of geography and the students of class XI IPS 2 MAN 1 Palu. Data collection techniques used in this research are a questionnaire (questioner), interview, and documentation. The results showed that the geography teacher role as a motivator in the formation of character values of students of class XI IPS 2 MAN 1 Palu, teachers play a role in guiding students in the learning process, the teacher stressed to do any given task, teachers ban students cheat well it's in the task and in Deuteronomy, as well as the teacher told the students to collect the task on time, teachers guide the activities of students which is associated with religious as fixed reminiscent of prayers to the students, although the learning is done online, and always pray before the start of learning. However, in practice, there are inhibiting factors faced by teachers of geography, namely the lack of attention of parents of students in the house to guide her but only expect fully to the teacher to guide the students.